2007
DOI: 10.1007/s11746-007-1063-3
|View full text |Cite
|
Sign up to set email alerts
|

Low‐trans Shortening and Spread Fats Produced by Electrochemical Hydrogenation

Abstract: Partially hydrogenated soybean oils were prepared by electrochemical hydrogenation at a palladium/cobalt or palladium/iron cathode, moderate temperature (70-90°C) and atmospheric pressure. The trans fatty acid (TFA) contents of 90-110 IV products ranged from 6.4 to13.8% and the amounts of stearic acid ranged from 8.8 to 15.4% (the higher stearic acid contents indicated that some reaction selectivity had been lost). The solid fat values and melting point data indicated that electrochemical hydrogenation provid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 9 publications
1
21
0
Order By: Relevance
“…Use of electrochemical hydrogenation instead of gas hydrogenation has been reported and developed for edible oil since 1992 [11]. Many studies have demonstrated that electrochemical hydrogenation offers an advantage of producing final product with trans isomer fatty acids at lower levels than gas hydrogenation and subsequently much less thermal degradation, which could significantly reduce the consumer's concerns [12,13]. In the process of electrochemical hydrogenation, the charge carried by the electron is involved in the reactions of various hydrogen donors and solvents, and the hydrogen concentration on the catalyst surface can be partially controlled by the applied current.…”
Section: Introductionmentioning
confidence: 99%
“…Use of electrochemical hydrogenation instead of gas hydrogenation has been reported and developed for edible oil since 1992 [11]. Many studies have demonstrated that electrochemical hydrogenation offers an advantage of producing final product with trans isomer fatty acids at lower levels than gas hydrogenation and subsequently much less thermal degradation, which could significantly reduce the consumer's concerns [12,13]. In the process of electrochemical hydrogenation, the charge carried by the electron is involved in the reactions of various hydrogen donors and solvents, and the hydrogen concentration on the catalyst surface can be partially controlled by the applied current.…”
Section: Introductionmentioning
confidence: 99%
“…The conductivity of the anode electrolyte changed in the same manner as the cathode. More H + was generated by the electrolysis of H 2 in the anode, which increased the conductivity of the system (List et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…More H + was generated by the electrolysis of H 2 in the anode, which increased the conductivity of the system (List et al, 2007).…”
Section: Conductivity Of the Electrolytementioning
confidence: 99%
“…The typical ranges of SFC for commercial bakery shortening were 23-40% at 10°C, 16-30% at 21.1°C, 13-27% at 26.7°C, 9-21% at 33.3°C, and 3-11% at 40°C. [11,12] Analysis of crystal polymorphism by X-ray diffraction…”
Section: Compatibility and Plasticitymentioning
confidence: 99%